Odpowiedzi

2010-03-25T17:09:41+01:00
5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x= 5/8 (w ułamku) ;P

3( x -1)=0
3x-3=0
3x=0+3
3x=3/:3
x=1

-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/:-6
x=-5

-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:-10
x= 3/2= 1 cała i 1/2 ( w ułamku)

4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:-2
x= - 5

Pozdro ;)
2010-03-25T17:13:17+01:00
A) 5x+2=7-3x / +3x
8x+2=7 / -2
8x=5 / :8
x=5/8

b) 3( x -1)=0
3x-3= 0 / +3
3x=3 / : 3
x=1

c) -6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/:-6
x=-5

d) -7(x-2)=3x-1
-7x-9=3x-1 / +9
-7x=3x-10 / -3x
-10x=-10 / : (-10)
x=1

e) 4(x-1)=6(1+x)
4x-4=6+6x / +4
4x=10+6x / -6x
-2x=10 / :(-2)
x= -5

liczę na naj ;)
2010-03-25T17:14:21+01:00
5x+2=7-3x /-2
5x=5-3x /+3x
8x=5 /8
x=0,625

3( x -1)=0
3x-3=0 /+3
3x=3 /3
x=1

-6(x+1)=24
-6x-6=24 /+6
-6x=30 /-6
x=-5

-7(x-2)=3x-1
-7x+14=3x-1 /-14
-7x=3x-15 / -3x
-10x=-15 /(-10)
x=1.5

4(x-1)=6(1+x)
4x-4=6+6x /+4
4x=10+6x /-6x
-2x=10 /(-2)
x=-5